Instruction through translanguaging in triglossic classroom contexts of Midlands province in Zimbabwe - Nhongo, Raphael; Siziba, Liqhwa P. (Penerbit Universiti Kebangsaan Malaysia, 2022)
In the Midlands province of Zimbabwe, there are mainly three languages, Shona, Ndebele, and English that are used in schools although at home it is mainly Shona and Ndebele. Midlands lies right on the isogloss where Shona is predominant on one side and Ndebele on the other. The paper scrutinises how translanguaging as a method of teaching takes place in a situation where there are three languages at play but such languages are not at par. Shona and Ndebele are the learners’ first languages where some learners are conversant with both and some with one of the two, and English is the main language of instruction. The paper also problematizes the idea of diglossia and that of a clearly defined isogloss in the Midlands province. Qualitative research approach guides all the methodological trajectories followed in this paper. Semi-structured interviews were the key data gathering tools from teachers in both peri-urban and the urban settings of the Midlands province capital, Gweru. The theory guiding this study is dynamic bilingualism. The results of the study revealed that in facilitating learning through translanguaging in a triglossic situation, teachers face challenges of balancing the languages and as a result code switching dominates the translanguaging process. It is therefore concluded that language inequalities in multilingual settings have negative impacts when it comes to translanguaging and negatively affects the learning process where other learners feel side lined on the grounds of their first language.